Stability in repeated matching markets - Ce Liu (Theoretical Economics, 2023)
This paper develops a framework for studying repeated matching markets. The model departs from the Gale-Shapley matching model by having a fixed set of long-lived players (firms) match with a new generation of short-lived players (workers) in every period. I define history-dependent and self-enforcing matching processes in this repeated matching environment and characterize the firms' payoffs. Firms fall into one of two categories: some firms must obtain the same payoff as they would in static stable matchings, and this holds at every patience level; meanwhile, repetition and history dependence can enlarge the set of sustainable payoffs for the other firms, provided that the firms are sufficiently patient. In large matching markets with correlated preferences, the first kind of firms corresponds to ``elite'' firms that make up at most a vanishingly small fraction of the market. The vast majority of firms fall into the second category.
Keywords: C71; C72; C73; C78; D47; 330; Gale-Shapley; matching; repeated games; stability